BIAYA PRESERVASI JALAN AKIBAT TRUK DENGAN BEBAN BERLEBIH DI JALAN PESISIR TIMUR PROVINSI ACEH - Fithra, Herman; M. Saleh, Sofyan (Jurnal Transportasi, 2011)
Aceh province heavily relies on the road transportation to support its economic development. Freight movement carried out by land transport (mostly on road) is more than 95% in this province. This condition is even worsened by trucks which tend to carry overload. This study is conducted to evaluate pavement performance in the east corridor of roads in the Aceh Province caused by overloading trucks, using the AASHTO method. The pavement preservation cost analysis is based on the pavement design life of 10 years. The results show that the preservation costs for 2-axle colt truck is Rp. Rp. 847/ton-km, for 2-axle engkel truck is Rp. 1,377/ton-km, for 3-axle tronton truck is Rp. 789/ton-km, and for 3-axle intercooler truck is Rp. 1,086/ton-km.Keywords: Aceh, preservation, performance, damage, highway.